(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
This study explores the global impact of integrating Artificial Intelligence (AI) in education and its implications for educational reform. Through a comprehensive meta-analysis of studies from Scopus indexed journals, the effects of AI on student learning outcomes, teaching practices, pedagogical approaches, and educational policy are examined. The findings indicate that AI integration in the classroom has the potential to significantly enhance student learning outcomes. AI-powered adaptive learning platforms and intelligent tutoring systems provide personalized instruction and differentiated learning experiences, addressing individual student needs and learning styles. The integration of AI also facilitates data-driven decision making, enabling teachers to make informed instructional choices based on student data analysis. Furthermore, the integration of AI influences teaching practices by promoting personalized instruction, facilitating collaborative learning, and supporting assessment and feedback processes. AI technologies enable teachers to adopt student-centered instructional approaches, promote collaboration among students, and provide timely and objective feedback to enhance student learning and growth. The implications of integrating AI in education for educational policy and reform on a global scale are discussed. It calls for a paradigm shift in educational systems, redefining curriculum, learning outcomes, and assessment practices. Policy guidelines should address ethical considerations, ensure equitable access to AI technologies, and prioritize comprehensive teacher training and professional development. This study contributes to understanding the transformative potential of integrating AI into education and provides insights for policymakers, educators, and researchers seeking to use AI technologies to improve teaching and learning outcomes globally.